PENGARUH KOMITMEN ORGANISASI, KEPUASAN KERJA DAN STRES KERJA TERHADAP KINERJA GURU DI SEKOLAH MENENGAH ATAS YPI AMIR HAMZAH MEDAN - Sufriady Halomoan Hasibuan; Suhandi .; Said Zainal Abidin; Muzakkir .; Koko Nugroho (Manajemen dan Bisnis, 2021)
This study aims to determine the effect of Organizational Commitment (X1), Job Satisfaction (X2) and Job Stress (X3) on Teacher Performance (Y) both partially and simultaneously at YPI Amir Hamzah High School Medan. This study uses a quantitative approach using a population and a sample of 48 teachers or respondents. The data collection techniques used are observation, interviews, questionnaires and documentation. The data analysis method used is Multiple Linear Regression Analysis. The results of the Multiple Linear Regression test partially show that Organizational Commitment with a significant value of 0.001, Job Satisfaction with a significant value of 0.027 and Job Stress with a significant value of 0.001 have a significant effect on teacher performance. In a simultaneous test, all independent variables have a significant effect on teacher performance, with a significant value of 0.000 0.05. It can be concluded that organizational commitment, job satisfaction and job stress have a significant effect on teacher performance at YPI Amir Hamzah High School Medan.